2015
DOI: 10.1007/s12223-015-0413-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of sophorolipids and their possible use as antiviral agents

Abstract: Sophorolipids are surface active glycolipids consisting of a hydrophilic sophorose unit and a hydrophobic portion composed of a fatty acid tail. Crude sophorolipid sample contains both acidic and lactonic forms of sophorolipid with different degrees of acetylation and varying lengths of the fatty acid chains depending on the substrates used in the production process. Carboxylic end in the acidic form of the fatty acid is free, whereas in the lactonic form, it is internally esterified. Sophorolipids show differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 32 publications
2
44
0
2
Order By: Relevance
“…; Borsanyiova et al . ). A study using natural SL mixtures with a variety of sugar head groups reported antimicrobial activity against a range of predominately Gram‐positive bacteria (Shah and Prabhune ).…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Borsanyiova et al . ). A study using natural SL mixtures with a variety of sugar head groups reported antimicrobial activity against a range of predominately Gram‐positive bacteria (Shah and Prabhune ).…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
“…Lactonic forms are more hydrophobic (Borsanyiova et al . ) and have been reported to have better biocide activities (Ito et al . ) as well as spermicide, cytotoxic and pro‐inflammatory activities.…”
Section: Classification and Structure Of Microbial Biosurfactants Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Sophorolipids (SLs), produced by a number of yeasts such as Candida bombicola , are a class of naturally derived glycolipid compounds containing a hydrophilic moiety and a hydrophobic moiety (Borsanyiova et al, 2016). They are biodegradable, exhibit low-toxicity and are environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…1618 SLs are also antiviral 19 and can modulate the severity of sepsis. 20 However, their potential for CNS applications has not yet been explored.…”
mentioning
confidence: 99%